El personal brand y estrategias para generación de contenido en Instagram. Caso @jennycomunica. - Aguirre Sánchez, Jenniffer Lizbeth (Machala, 2021)
Instagram is a social network in increase, its facilities to generate content through images, reels, videos, stories, etc., has become one of the most followed by the millennial population, even allowing the opening to new possibilities for digital communication and e-commerce. The objective of this research is to develop content generation strategies for personal branding of the instagram account @jennycomunica. This will be based in the first instance on the descriptive mixed analysis of public instagram accounts with a certain level of followers, which should handle their own content, if possible related to professional aspects or self-improvement. Then we will work on the application of communicational strategies in an experimental way in @jennycomunica, the results obtained from this process will allow us to contrast the main aspects of the theory with the professional praxis. It is expected as a result to apply actions in an organic and paid way that allow the increase of followers, analyze the engagement, the measurement of interaction with the generated content; this in turn allows to expand the opportunities for monetization and be the basis for the future generation of an online business.
Instagram es una red social en incremento, sus facilidades para generar contenidos a través de imágenes, carretes, videos, historias, etcétera, la ha convertido en una de las más seguidas por la población millenial, incluso permitiendo la apertura a nuevas posibilidades para la comunicación digital y el comercio electrónico. En la presente investigación tiene como objetivo el desarrollar estrategias de generación de contenido para personal brand de la cuenta de Instagram @jennycomunica. Para esto se basará en primera instancia en el análisis mixto descriptivo de cuentas públicas de instagram con cierto nivel de seguidores, las mismas que deberán manejar contenidos propios, de ser posible relacionados con aspectos profesionales o de superación personal. Luego se trabajaría en la aplicación de estrategias comunicacionales de manera experimental en @jennycomunica, los resultados que se obtengan de ese proceso permitirán contrastar los aspectos principales de la teoría con la praxis profesional. Se espera como resultado aplicar acciones de manera orgánica y de pago que permitan el incremento de los seguidores, analizar el engagement, la medición de interacción con los contenidos generados; esto a su vez permite que se expandan las oportunidades para monetización y sea la base para la futura generación de un negocio online.
Keywords: INSTAGRAM; COMUNICACION DIGITAL; CONTENIDO; RED SOCIAL